Turbo C/C++ : the complete reference - Schildt, Herbert (Berkeley, California : Osborne McGraw-Hill, 1992)
The author carefully lays out the concepts of C programming in this excellent reference and tutorial that presents C as a block structured middle level language. Written for programmers at all skill levels, it describes every Turbo C, Turbo C++, and Borland C++ command and function. Loaded with examples and programming techniques, it would be useful to any C programmer. Appendices cover using the debugger, interfacing to assembly language, global variables. Annotation copyright Book News, Inc. Portland, Or.
Introduction -- Part I. The C language -- Part II. The turbo C environment -- Part III. The library -- Part IV. Turbo/Borland C++ -- Part V. The Turbo/Borland C++ environment -- Part VI. Windows programming using Borland C++ -- Part VII. Appendices -- Index.
Includes bibliographical references and index.
Keywords: TURBO C (COMPUTER FILE)